Analisis Kelayakan Investasi Perbaikan Kualitas Pelayanan Di AJB Bumi Putera 1912 Cabang Sidoarjo - Ngatilah, Yustina; Parwati, C. Indri (Department Industrial Engineering, University of Muhammadiyah Malang, 2011)
Customer satisfaction is the main thing that must be considered by every company, both service and production, so customers do not switch keperusahaan competitors, and customer satisfaction always changing according to the era or the era of human development. In terms of customer satisfaction that this changing, we need quality improvement program. This study used the method ROQ (Retrun On Quality), namely, the methods used for decision making will improve the quality of the proposed program, can be used or not. ROQ very to influence by the amount of customer satisfaction, customer retention and cost of the proposed program of quality improvement. In determining the quality improvement program proposal, use graph mapping IP From research result shows an increase in customer satisfaction and customer retention, each of which is 80.41% to 81.22% and 24.56% to 28.56%, which reached the stage These proposals deserve diimpelementasikan quality improvement program. By using the data market growth, market share data, the average benefits agents and the interest rate at the time of planning time, then the calculation can be done ROQ.ROQ calculations, requiring the calculation of NPV, NPV0, NPVAS conducted as a planning horizon of 5 periods ahead. From the calculation results, obtained NPV Rp.152.636.602.289, 00; NPV0 for Rp.145.407.658.197,00; and NPVAS of Rp.3.573.189.670, 00; so ROQ value of 2.0231. The result was states that the proposal is feasible quality improvement program to be implemented, until rate reached 46.457%.